Peranan Dinas Lingkungan Hidup Dalam Pengelolaan Sampah Di Kecamatan Rambah Kabupaten Rokan Hulu - Muhammad Fahrizal Hasibuan (Pustaka Galeri Mandiri, 2021)
The purpose of this research is to know the role of environment department in waste management and to know its obstacles of environment department in rambah subdistrict. This research use qualitative research that produces descriptive data in the form of a writen words or oral from people and the observed. from the research results obtained the role of environmental services in reducing waste are by formulating programs and socialization in community about the dangers of waste. the role of environmental services in the utilization of waste by forming a garbage bank, garbage care group and amenities. The environment department strives to provide quality facilities and infrastructure and conducts community guidance and supervision on waste. While the environmental service barriers to waste management are the lack of waste facilities, the number of garbage transportation fleet that has not been maximized, the technique of garbage collection is less rapid and there is no regulation on waste management. From the results of interviews with informants and results of observations concluded that the role of environmental department is quite accomplished with the real effort even though the field is not maximized results